Alumina supported carbon composite material with exceptionally high defluoridation property from eggshell waste - Lunge, Sneha; Thakre, Dilip; Kamble, Sanjay; Labhsetwar, Nitin K.; Rayalu, Sadhana (Journal of Hazardous Materials, 2012)
A new alumina supported carbon composite material called ``Eggshell Composite'' (EC) was synthesized from eggshell waste as calcium source for selective fluoride adsorption from water. The effect of various synthesis parameters like eggshell (ES): Eggshell membrane (ESM) ratio, aluminium loading, mixing time and calcinations temperature to optimize the synthesis conditions for selective fluoride removal has been studied. It was observed that the synthesis parameters have significant influence on development of EC and in turn on fluoride removal capacity. EC synthesized was characterized for elemental composition, morphology, functionality and textural properties. Results showed that EC obtained from eggshell modified with alumina precursor is more selective and efficient for fluoride removal. Langmuir and Freundlich isotherm were used to obtain ultimate fluoride removal capacity. The calcium and alumina species in EC shows synergistic effect in fluoride adsorption process. Fluoride sorption studies were carried out in synthetic, groundwater and wastewater. EC proved to be a potential, indigenous and economic adsorbent for fluoride removal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Composite material; Eggshell; Eggshell membrane; Fluoride adsorption; Langmuir